Math Remediation: How Repeatedly Failed Students Perceive The Remediation Program and Their Failures - Simamora, Rustam Effendy; Darmayasa, Jero Budi (Universitas Sarjanawiyata Tamansiswa, 2024)
Mathematics remediation (MR) is crucial in higher education, serving as a cornerstone to prepare under-equipped students. However, numerous Mathematics Education students in one of the public universities in Indonesia have repeatedly failed in this program. Failure experiences have an essential role in pre-service mathematics teachers' personal and professional development. While some research has explored the students' failure experiences, a significant gap exists in exploring the perception of repeatedly failed students in MR. Our qualitative narrative case study delves into the perceptions of repeatedly failing students regarding the MR and their failures. Five themes emerged through analysis of reflective writing and interview data: perceptions of mathematics and its learning, perspectives on the MR program, attitudes toward failure, factors contributing to participant failures, and expectations for MR program development. This study provides valuable insights to enhance the effectiveness of MR, shedding light on the intricate dynamics surrounding students' experiences with the program.